Penyelesaian Sengketa Wanprestasi Melalui Jalur Mediasi dalam Perkara Utang Piutang Putusan No. 69/Pdt.G/2025/PN SDK - Anita Sunny Rachmania; Erika Esteria Pasaribu; Nisa Auliya Ahmad; Siti Nur’Aini (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This paper examines the resolution of a civil dispute in Decision Number 69/Pdt.G/2025/PN Sdk, which concluded with a peace deed (akte van dading) between the Semeru Civil Servants Savings and Loan Cooperative and the defendant. This study employs a normative juridical method by analyzing the court decision, the Indonesian Civil Code provisions, and regulations issued by the Supreme Court regarding mediation and settlement agreements. The findings reveal that a peace agreement constitutes an effective dispute resolution mechanism, as it obtains permanent legal force once ratified by the court. The decision demonstrates that a settlement can legally terminate the parties’ obligations as long as it fulfills the validity requirements of a contract under Article 1320 of the Indonesian Civil Code and does not violate law or public order. Therefore, peace agreements play a significant role in the law of obligations as a fast and efficient alternative dispute resolution method that emphasizes a win–win solution for the parties involved.